Analisis Penggunaan Authentic Assesment sebagai Alat Pengukuran Perkembangan Anak Usia Dini - Amanda, Rizki Surya; Hasni, Uswatul; Indriyani, Indriyani (Mitra Ash-Shibyan: Jurnal Pendidikan dan Konseling, 2024)
Assessment in early childhood aims to collect and provide important information to educators, parents and families about development and growth of children. The information is then used to plan educational activities that children can learn and understand. However, early childhood teachers often experience difficulties in carrying out assessments due to the different characteristics of children. This study aims to analyze the implementation of authentic assessment by Early Childhood Education (ECE) teachers. This study is descriptive-qualitative research. This research was conducted in 5 ECE institutions consisting of 4 Playgroups and 1 ECE Post in Telanai Pura Sub-district, Jambi City. Data were collected using open-ended questionnaires, interviews, and documentation. The data were then analyzed through three stages, namely data reduction, data presentation, and data verification. The results of the study explain that 1) the implementation of authentic assessment was carried out every day; 2) the application of authentic assessment was done through work assessment; and 3) the supporting factor for the application of authentic assessment is the availability of lesson plans; while the inhibiting factor is that not all children can be observed in 1 day.